2008
DOI: 10.1111/j.1570-7458.2008.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of latex and its constituent defensive chemistry in milkweeds (Asclepias): a phylogenetic test of plant defense escalation

Abstract: A tremendous diversity of plants exude sticky and toxic latex upon tissue damage, and its production has been widely studied as a defensive adaptation against insect herbivores. Here, we address variation in latex production and its constituent chemical properties (cardenolides and cysteine proteases) in 53 milkweeds [ Asclepias spp. (Apocynaceae)], employing a phylogenetic approach to test macroevolutionary hypotheses of defense evolution. Species were highly variable for all three traits, and they showed lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 73 publications
1
64
1
Order By: Relevance
“…(24) and latex (29) showed declining expression during the diversification of Asclepias, trichomes showed no trend (30), and phenolics and plant tolerance to damage showed evidence for escalation (7,24). In this new, larger dataset we have evaluated not only the presence of directional trends in these and other traits, but importantly have evaluated the tempo of evolutionary changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(24) and latex (29) showed declining expression during the diversification of Asclepias, trichomes showed no trend (30), and phenolics and plant tolerance to damage showed evidence for escalation (7,24). In this new, larger dataset we have evaluated not only the presence of directional trends in these and other traits, but importantly have evaluated the tempo of evolutionary changes.…”
Section: Resultsmentioning
confidence: 99%
“…3). As an index of overall defense investment, we also assess trait evolution of the sum of the Z-scores (standard normal scores) for cardenolides, latex, and trichomes (29,31). Although this approach certainly omits some potentially important defensive traits of milkweeds (e.g., phenolics, cysteine proteases, waxes), given our previous demonstration of covarying evolution of milkweed Models were fit under 2 modes of evolution: gradual, in which phylogenetic distance is scaled as time, and speciational, in which phylogenetic distance is scaled as number of nodes (speciation events).…”
Section: Resultsmentioning
confidence: 99%
“…Specialist herbivores in particular may have found ways to suppress plant defenses (Box1) or to circumvent them via behavioral adaptations, which, in analogy to the PTI/ETI model in plant-pathogen interactions, may have led to the counter-evolution of specifically adapted defense mechanisms in plants [120, 121]. Until today, few mechanistic examples of plant-counter adaptations to specialists are known (but see other articles in this special issue), and further research is required to disentangle whether differential responses of plants to chewing herbivores are truly specific, and whether plants have evolved to tailor their response to different chewing attackers.…”
Section: Do Recognition-induced Plant Hormone Network Trigger Specifmentioning
confidence: 99%
“…In Asclepias, complex cardenolides appear to be phylogenetically novel (8). Nevertheless, one of the few studies to use explicit phylogenetic models of character evolution actually reported a pattern of phyletic decline of defensive cardenolides in Asclepias (9,10).…”
mentioning
confidence: 99%